Price-based measurement of financial globalization: A cross-country study of interest rate parity - Hiro Ito; Menzie Chinn (University of California, Santa Cruz Institute for International Economics (SCIIE), 2007)
We characterize the relationship between ex post exchange rate depreciation and the interest differential for a set of countries that spans both developed and emerging market economies. Measured ex post uncovered interest differentials are then related to measures of trade and financial openness, financial development, government budget balances, institutional development, and exchange rate regimes. We find that there is wide diversity in the coefficient relating depreciations and interest differentials. Some of these differing results can be attributed to differences in inflation rate, inflation volatility, capital account openness, legal development, and the nature of the exchange rate regime.
Keywords: F31; F41; 330; uncovered interest parity; exchange rates; financial market integration; emerging markets; Zinsparität; Wechselkurs; Finanzmarkt; Globalisierung; Marktintegration; Schätzung; Welt